SIMULATION-ROLE LEARNING AS A PROCESS IMPROVING COMMUNICATIVE CULTURE STUDENTS OF ECONOMIC HIGH SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
Те article deals the problems komynikechin culture? It shows factors which influence on the level of skill.